Gastropod Community Structure in Seagrass Waters in Panjang Island, Jepara, Central Java - Tri Adi Nugroho; Ria Azizah; Ali Djunaedi; Delianis Pringgenies (Masyarakat Moluska Indonesia, 2020)
Seagrass is a community that consists a large number of organisms which associated within. Organisms associated with seagrass are gastropods. The purpose of this research is to determine the structure of gastropods community at seagrass on Pulau Panjang, Jepara. Exploration methods was applied and data was analyzed descriptively. The location of research are divided into 3 locations based on 3 different densities of seagrass : sparse, medium and dense. Every location consists of 4 stations with 3 repetitions. The research was held during Desember 2014. Sampling using quadratic a frame size of 1x1 m. The result, there are were 15 genera gastropods of 8 families as followed Trochus (Ciridae), Strombus (Strombidae), Turbo, Astralium, Dentarene, Liotina (Turbinidae), Cantharus, Nassaria, Engina (Buccinidae), Cerithium, Rhinoclavis, Clypeomorus (Cerithiidae), Morulla (Muricidae), Columbella (Columbellidae), and Neritodryas (Neritidae). The abundance in location I 108.75 ind/????2 with dense of seagrass density, location II 91 ind/m2 with medium of seagrass density, and location III 47,25 ind/m2 with rare of seagrass density. Index value of Gastropod diversity classified medium category, index value of gastropod similarity classified high category, it means abudance from each spesies can be said to be similar, and evenly distributed and not on domination by a specific species. Community similarity index classified in the category of medium to very large